Preserved Electroencephalogram Power and Global Synchronization Predict Better Neurological Outcome in Sudden Cardiac Arrest Survivors - Ho, Li-Ting; Serafico, Bess Ma. Fabinal; Hsu, Ching-En; Chen, Zhao-Wei; Lin, Tse-Yu; Lin, Chen; Lin, Lian-Yu; Lo, Men-Tzung; Chien, Kuo-Liong (Frontiers in Physiology, 2022)
Quantitative EEG (qEEG) delineates the complex brain activities. Global field synchronization (GFS) is one multi-channel EEG analysis that measure global functional connectivity through quantification of synchronization between signals. We hypothesized that preservation of global functional connectivity of brain activity might be a surrogate marker for good outcome in sudden cardiac arrest (SCA) survivors. Additionally, we examined the relation of phase coherence and GFS in a mathematical approach. We retrospectively collected EEG data of SCA survivors in one academic medical center. We included 75 comatose patients resuscitated following in-hospital or out-of-hospital non-traumatic cardiac arrest between 2013 and 2017 in the intensive care unit (ICU) of National Taiwan University Hospital (NTUH). Twelve patients (16%) were defined as good outcome (GO) (CPC 1-2). The mean age in GO group was younger (51.6±15.7 vs. 68.1±12.9, P<0.001). We analyzed standard EEG power and computed EEG GFS and assessed the cerebral performance category (CPC) score 3 months after discharge. Alpha band showed the highest discrimination ability (area under curve [AUC] =0.78) to predict GO using power. Alpha band GFS showed the highest AUC value (0.8) to predict GO in GFS. Furthermore, by combining EEG power+GFS, the alpha band showed the best prediction value (AUC 0.86) in predicting GO. The sensitivity of EEG power+GFS was 73%, specificity was 93%, PPV was 0.67, and NPV was 0.94. In conclusion, by combining GFS and EEG power analysis, the neurological outcome of the non-traumatic cardiac arrest survivor can be well predicted. Furthermore, we proved in mathematical view point that although both amplitude and phase contribute to obtaining GFS, interference in phase variation drastically changes the possibility of generating good GFS score.